High-Dimensional Mediation Analysis Based on Additive Hazards Model for Survival Data - Cui, Yidan; Luo, Chengwen; Luo, Linghao; Yu, Zhangsheng (Frontiers in Genetics, 2021)
Mediation analysis has been extensively used to identify potential pathway between the exposure and outcome. However, the analytical methods of high-dimensional mediation analysis for survival data are still yet to be promoted, especially for non Cox model approaches. We propose a procedure including "two-step" variable selection and indirect effect estimation for additive hazards model with high-dimensional mediators. We first apply sure independence screening and smoothly clipped absolute deviation regularization to select mediators. Then we use Sobel test and the BH method for indirect effect hypothesis testing. Simulation results demonstrate its good performance with higher true positive rate and accuracy, as well as lower false positive rate. We apply the proposed procedure to analyze DNA methylation markers mediating smoking and survival time of lung cancer patients in a TCGA cohort study. The real data application identifies four mediate CpGs, three of which are newly-found.